The Effect of Work from Home (WFH) and Work Discipline on Employee Performance Through Work-Life Balance (WLB) in the Covid-19 Pandemic: Explanatory Study at BPKAD Office, Bondowoso Regency - Novita Ekasari; Meirani Harsasi; Rini Yayuk Priyati; Nurul Qomariah (AIBPM Publisher, 2022)
This study aims to empirically examine the effect of work from home and work discipline on employee performance through work-life balances during the COVID-19 pandemic. The population of this study was all employees of the Bondowoso Regency BPKAD. Collecting data using a questionnaire. The results showed an effect of work from home on employee performance. There is an influence of work discipline on employee performance. There is an effect of work from home on work-life balance. There is a disciplinary effect on work-life balance. There is an effect of work-life balance on employee performance. There is an effect of work from home and work discipline on employee performance through work-life balance.Keywords: Work from Home, Work discipline, Employee Performance, Work-Life Balance, COVID-19 pandemic.